The Application of TPACK (Technological Pedagogical Content Knowledge) in English Teaching Using Schoology - Inggraini Hartono; Siti Mina Tamah (Indonesia Technology Enhanced Language Learning (iTELL) Association, 2025)
This study aims to find out their application of TPACK (Technological Pedagogical Content Knowledge) using Schoology and explored the impacts Schoology-based English teaching have on teachers and students. The study employed two methods: class observation and interview by involving three English teachers and forty-five students aged 15-17 years old from a private middle school in Indonesia. This study reveals that the positively perceived advantages outnumber the perceived disadvantages, making Schoology still the recommended LMS to be used in schools to implement TPACK. Regarding the application of TPACK in Schoology-based English instruction found in this study, the teacher-centeredness is still present in the delivery of material via PowerPoint and only one learning model is used throughout the lesson. Thus, it is recommended for schools to plan for prior TPACK and Schoology training to maximize the use of TPACK and Schoology features.